1991
DOI: 10.1091/mbc.2.12.1057
|View full text |Cite
|
Sign up to set email alerts
|

Alpha 2-macroglobulin restricts plasminogen activation to the surface of RC2A leukemia cells.

Abstract: Human RC2A myelomonocytic leukemia cells are able to activate the prourokinase (pro-u-PA) they secrete so that active u-PA is present both in serum-free conditioned medium from these cells, as well as on the cell surface. When the cells are grown in serum-containing medium, no u-PA activity can be found in the medium but active u-PA is found bound to the cell surface where it can generate bound plasmin. This distribution of u-PA activity was shown to be, first, the net result of slow inactivation of free activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In this regard several groups have demonstrated that surface localization of plasminogen and prouPA promotes their activation and affords relative protection against plasma proteinase inhibitors (Stephens et al, 1989;Ellis et al, 1990). More recently Stephens et al (1991) observed that twochain uPA on human RCBA promyelomonocytic leukemia cells was protected from inactivation by alpha2macroglobulin (azM). As a2M is believed to be a scavenger for TGF-fl as well (O'Connor-McCourt et al, 1987;Huang et al, 19881, cell-surface localization of the activation complex for LTGF-p may have the additional advantage of prolonging the local half-life of TGF-p.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard several groups have demonstrated that surface localization of plasminogen and prouPA promotes their activation and affords relative protection against plasma proteinase inhibitors (Stephens et al, 1989;Ellis et al, 1990). More recently Stephens et al (1991) observed that twochain uPA on human RCBA promyelomonocytic leukemia cells was protected from inactivation by alpha2macroglobulin (azM). As a2M is believed to be a scavenger for TGF-fl as well (O'Connor-McCourt et al, 1987;Huang et al, 19881, cell-surface localization of the activation complex for LTGF-p may have the additional advantage of prolonging the local half-life of TGF-p.…”
Section: Discussionmentioning
confidence: 99%
“…uPA activity may also be lost from the cell-surface by plasmin cleavage at Lys135-Lys136 in the A-chain of uPA, leaving only the so-called amino terminal fragment (ATF) bound on the cell. The general plasma proteinase inhibitor, a2-macroglobulin, inactivates soluble uPA relatively slowly, but uPA bound to uPAR is apparently protected by a steric effect (46), thus allowing plasminogen activation to occur on the surface of cells even in the presence of serum (29).…”
Section: Biochemistry Of the Urokinase Plasminogen Activation Systemmentioning
confidence: 99%
“…a 2 -Macroglobulin binds plasminogen activators and their inhibitor complexes as well as plasmin. Cell-bound plasmin is protected from a 2 -macroglobulin [85]. The discovery that plasmin solubilizes the fibrin network led to the utilization of plasminogen activators as thrombolytic agents in cardiovascular diseases and ischemic stroke [19,86].…”
Section: Pai-1 and Pai-2mentioning
confidence: 99%